Flood risk management in the coastal city of Lagos, Nigeria. Issue 3 (1st July 2015) - Adelekan, Ibidun O.
Abstract: An increasingly important threat to the high population and large concentration of residential, industrial, commercial and urban infrastructure systems in Africa's coastal megacity of Lagos is flooding. Over the past decade, flooding in Lagos has increased significantly, drawing increasing attention to the need for flood risk management. The paper examines the current approach to flood risk management by public and private agents in the city in the context of international flood risk management practices. The implications of existing flood management for future flood risks are also discussed.